2021
DOI: 10.3390/prosthesis3010009
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Canine-Guided Occlusion with Other Occlusal Schemes in Removable Complete Dentures: A Systematic Review

Abstract: Choosing an adequate occlusion is challenging during the construction of artificial dentures, and critical for patient satisfaction. However, there is no conclusive evidence to support which occlusal design is more appropriate. The aim of this systematic review was to evaluate canine-guided occlusion in comparison to other occlusal schemes in removable complete denture wearers. The review was conducted according to the Preferred Reported Items for Systematic Review and Meta-Analysis (PRISMA) guidelines. An ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…32 One other study was identified from the nonpeer-reviewed literature and was included. 19 A total of 10 systematic reviews were included in this overview (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…32 One other study was identified from the nonpeer-reviewed literature and was included. 19 A total of 10 systematic reviews were included in this overview (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…All systematic reviews 6,7,11,[17][18][19][20][21][22][23] included randomized clinical trials, and 5 reviews also included prospective studies. 18,[20][21][22][23] In addition to clinical studies, 2 reviews included other systematic reviews, 11,20 1 included an in vitro study, 22 removable denture or implants.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations